PENGARUH JARAK RUJI MESIN PENGUPAS KACANG TANAH TERHADAP KUALITAS HASIL KUPASAN - Xander Salahudin; Sri Widodo (Universitas Tidar, 2018)
The land area of peanut plantations reached 314 Ha, making Tegalrejo District a peanut center in Magelang Regency. As a center for producing peanuts, the demand for peanuts in Tegalrejo District is also high. The high demand makes the need for the application of technology in producing peeling peanuts. Based on the problems faced and the existing literature review, it is necessary to develop a peanut stripper that is good in stripping capacity and the quality of the peel. The purpose of this study was to analyze the effect of the distance between peanut peeling machine on the quality of the peel. The study was conducted with 3 repetitions with 1 kg of peanuts per data collection. The results obtained from the study are variations in the distance of 15 mm of test yielding the highest percentage of peanut peanut value of 80.96%. Whereas the highest capacity is obtained by varying the 20 mm peanut peeling distance, which is 28.48 kg/hour.